Weed Control in Beans and Peas (Bush, Pole, Lima Beans, English Peas and Southern Peas) - William M. Stall (EDIS, 2006)
Revised! HS-188, a 5-page fact sheet by William M. Stall, describes effective weed management practices for beans and peas in Florida and provides a table listing herbicides available to growers for chemical weed control. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.